Effect of infarct stiffness on non-infarcted left and right ventricular tissue remodeling: a computational study based on myocardial mechano-transduction. (25th November 2020) - Koopsen, T; Van Osta, N; Willemen, E; Van Nieuwenhoven, F.A; Gorcsan, J; Prinzen, F.W; Arts, T; Delhaas, T; Lumens, J
Abstract: Background/Introduction: The mechanical properties of infarcted myocardium are important determinants of cardiac pump function and risk of developing heart failure following myocardial infarction (MI). Purpose: To better understand the effects of infarct stiffness on compensatory hypertrophy and dilation of non-infarcted tissue in the left (LV) and right ventricle (RV), by using a computational model. Methods: The CircAdapt computational model of the human heart and circulation was applied to simulate an acute MI involving 20% of LV wall mass. The simulation was validated using previously published experimental data. Subsequently, two degrees of increased infarct stiffness were simulated. In all three simulations, a model of structural myocardial adaptation of the non-infarcted tissue was applied, based on sensing of mechanical loading of myocytes and extracellular matrix (ECM). Results: Mild and severe stiffening of the infarct reduced the increase of LV end-diastolic volume (EDV) from +23 mL to +17 mL and +16 mL, respectively, and the increase of LV non-infarcted tissue mass from +31% to +21% and +18%. RV EDV decreased after adaptation, and mild and severe infarct stiffening reduced the decrease of RV EDV from −21 mL to −12 mL and −10 mL, respectively. Increase of RV tissue mass was reduced from +13% to +8% and +7% with mild and severe infarct stiffening. In the LV, reduced dilation and hypertrophy were driven mainly by a reduction of maximum stress in the ECM and a higher stress between the myocytes and ECM following infarct stiffening. The decreased RV hypertrophy, but not EDV reduction, was caused by a reduction of maximum RV ECM stress and maximum RV active myofiber stress. Conclusions: Model simulations predicted that a stiffened LV infarct reduces both LV and RV non-infarcted tissue hypertrophy as well as LV dilation. In LV remodeling, maximum ECM stress and stress between myocyte and ECM played a more prominent role than in RV remodeling, while maximum active stress was more important in the RV. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was funded by the Netherlands Organisation for Scientific Research and the Dutch Heart Foundation.